PENGARUH PENGGUNAAN MEDIA SOSIAL, MODAL USAHA, DAN TENAGA KERJA TERHADAP PENDAPATAN UMKM KULINER DI KOTA JAMBI - Nabila Retha Susanti; Rosmeli; Nurhayani (Jurnal Riset Multidisiplin Edukasi, 2025)
The purpose of this study is to [1] determine the social and economic characteristics of culinary MSMEs, and [2] analyze the influence of the use of social media, business capital, and labor on the income of culinary MSMEs in Jambi City. This study utilizes primary data and secondary data using descriptive analysis and quantitative analysis. The dummy variable of this study is the use of social media. This study uses the multiple linear regression method. By using proportional stratified random sampling, the sample amounted to 99 units. Data were collected by sending questionnaires to each person who participated. The results of the descriptive analysis study are [1] Characteristics of culinary MSMEs based on gender, the average is female. Based on the average age group, it is 34 years. According to the last education group, the average is high school/vocational school. According to the occupational group, the average is informal. Based on the average length of business, it is 4 years. Based on the average initial business capital, it is Rp. 8,510,000. The average workforce group is 4 people. Based on the average monthly income, it is Rp. 9,620,000. The results of quantitative analysis research [2] show that business capital and labor variables have a significant influence, with the use of social media not having a significant influence on the income of culinary MSMEs in Jambi City.